A new and critical edition of George Osborn's The poetical works of John and Charles Wesley (1868-1872) with the addition of notes, annotations, biographical and background information. Volume II - Rogal, Samuel J. (Lewiston : Edwin Mellen Press, 2009)
This volume of the ?New Edition? of George Osborn?s nineteenth-century collection of The Poetry of John and Charles Wesley provides access to the original poems of the eighteenth-century Wesleys, as well as their translations and altered versions of others? poetical works. It provides necessary background information relative to those poems?details historical, bibliographical, and biographical that Osborn omitted or of which he had no knowledge.
Title from PDF title page (viewed on Nov. 21, 2012).
Description based upon print version of record.
Keywords: Hymns, English -- Texts; Religious poetry, English -- 19th century; POETRY / English, Irish, Scottish, Welsh; Electronic books